Physicochemical Characterization of Organic Matter in Bayer Liquor - Busetti, Francesco; Berwick, Lyndon; McDonald, Suzanne; Heitz, Anna; Joll, Cynthia; Loh, J.; Power, G. (American Chemical Society, 2014)
Organic matter in Bayer liquor from an alumina production facility in Australia was characterized in terms of its molecular weight distribution and molecular structure using a suite of complementary chromatographic, spectroscopic, and thermal and chemical degradation methods. The organic matter was characterized using high-performance size-exclusion chromatography with UV-vis detection (HPSEC-UV), Fourier transform infrared (FTIR) spectroscopy, and solid-state 13C nuclear magnetic resonance (13C NMR) spectroscopy. These techniques provided information on the apparent molecular weight distribution of the organic matter contained in the Bayer liquor, its alkyl/aromatic characteristics, and the presence of specific functional groups. The techniques of microscale sealed vessel (MSSV) pyrolysis-gas chromatography-mass spectrometry (GC-MS), flash pyrolysis-GC-MS, and online tetramethylammonium hydroxide (TMAH) thermochemolysis-GC-MS provided detailed information at a molecular level. Information on individual low-molecular-weight organic acids in the sample was also obtained using liquid chromatography- tandem mass spectrometry (LC-MS-MS). The novelty of this work is the molecular identification of nitrogen compounds, pyridines, pyrenes, quinolones, benzoquinolines, indoles, carbazoles, bipyridines, and phenylpyridines that derive from organic matter in the bauxite or its transformation products. The results from the other analysis techniques largely confirm the high aromatic content of the liquor, with varying degrees of alkyl (predominantly methyl), carboxylic, ketone, nitrile, and hydroxyl substitution. Aromatic acids were found to be abundant, although they were poorly detected using pyrolysis methods, highlighting the importance of using a suite of complementary techniques for the analysis of Bayer liquor samples.